A Bauer-Hausdorff Matrix Inequality. (4th December 2013) - Yan, Zizong; Wu, Shanhe
Abstract : We present a biorthogonal process for two subspaces of ℂ n . Applying this process, we derive a matrix inequality, which generalizes the Bauer-Hausdorff inequality for vectors and includes the Wang-IP inequality for matrices. Meanwhile, we obtain its equivalent matrix inequality.